2012
DOI: 10.1128/jvi.00751-11
|View full text |Cite
|
Sign up to set email alerts
|

p53 Degradation Activity, Expression, and Subcellular Localization of E6 Proteins from 29 Human Papillomavirus Genotypes

Abstract: Human papillomaviruses (HPVs) are the etiological agents of cervical cancer and other human malignancies. HPVs are classified into high-and low-risk genotypes according to their association with cancer. Host cell transformation by high-risk HPVs relies in part on the ability of the viral E6 protein to induce the degradation of p53. We report the development of a cellular assay that accurately quantifies the p53 degradation activity of E6 in vivo, based on the fusion of p53 to Renilla luciferase (RLuc-p53). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
89
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 74 publications
9
89
1
1
Order By: Relevance
“…38 Mesplede et al showed that E6 of HPV26, 70 and 82 and to a lesser degree E6 of HPV66, are able to degrade p53 with the same efficiency as HR-HPV types, while LR-HPV11 is not. 39 In addition to pHR-HPV types, our findings of p16 INK4a overexpression in cervical cancer cases with single transcription of the HR-HPV types 39, 51 and 56 that also occur in low frequency in cervical cancer, supports their classification as Group 1 carcinogens.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…38 Mesplede et al showed that E6 of HPV26, 70 and 82 and to a lesser degree E6 of HPV66, are able to degrade p53 with the same efficiency as HR-HPV types, while LR-HPV11 is not. 39 In addition to pHR-HPV types, our findings of p16 INK4a overexpression in cervical cancer cases with single transcription of the HR-HPV types 39, 51 and 56 that also occur in low frequency in cervical cancer, supports their classification as Group 1 carcinogens.…”
Section: Discussionsupporting
confidence: 60%
“…34,35 The multiplex type-specific E7 PCR utilizes HPV type-specific primers targeting the E7 region for the detection of 19 HR-/pHR (HPV16, 18,26,31,33,35,39,45, 51, 52, 53, 56, 58, 59, 66, 68a, 68b, 70, 73, 82) and 2 LRtypes (HPV6, 11), with detection limits ranging from 10 to 1,000 copies of the viral genome. 34 Two primers for the amplification of b-globin were also included to provide a positive control for the quality of the template DNA.…”
Section: Type-specific E7 Pcr-mpg (Ts-e7-mpg) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Mesplède and colleagues examined the ability of 29 different E6s, most from genus alpha, to target p53 for degradation and characterized their subcellular localization patterns (43). A separate study by Cornet and coworkers characterized the ability of various beta HPV E6 proteins to increase the life span of human keratinocytes and to alter p53 functions in beta HPV E6-expressing cells (14).…”
mentioning
confidence: 99%
“…The detection strategy for hrHPVE7 was based on five different assays: "recomWell HPV 16/18/45 KJhigh", "recomWell HPV 16/18/45 KJlow", "recomWell HPV 39/51/56/59", "recomWell HPV 16/31/33/35/52/58" and "recomWell HPV HR screen" (for 16,18,31,33,35,39,45, 51, 52, 56, 58 and 59 E7). Each assay refers to different combinations of hrHPVE7 or different concentrations of the relevant ELISA antibodies and yields a measurement of the optical density, a continuous variable.…”
Section: Hrhpve7 Testingmentioning
confidence: 99%